2016
DOI: 10.18311/ajprhc/0/6014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Microsporidial Infection in Immunocompromised Patients with Staining and Molecular Methods Based on Internal Transcribed Spacer Region Gene in Two Cities of Southwest Iran during 2013-2014

Abstract: Microsporidiosisis anopportunistic infection frequently diagnosed in immunocompromised patients. Microsporidiosis causes symptomatic or asymptomatic infections immunocompromised/immunosuppressed patients may experience severe and disseminated microsporidiosis. Fecal samples were taken from 186 patients with human immunodeficiency virus (86) and cancer (100). Microsporidia spp. were detected 27.9% (24/86) and 11.6% (10/86) in HIV + patients, 18% (18/100) and 7% (7/100) of cancer patients using polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Kazemi et al performed a study to identify the prevalence of microsporidiosis in the southwest of Iran. They reported both E. bieneusi and E. intestinalis in the samples [ 19 ]. In contrast, in a study in India, E. intestinalis was the most common cause of microsporidiosis in patients with diarrhea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kazemi et al performed a study to identify the prevalence of microsporidiosis in the southwest of Iran. They reported both E. bieneusi and E. intestinalis in the samples [ 19 ]. In contrast, in a study in India, E. intestinalis was the most common cause of microsporidiosis in patients with diarrhea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reports on the incidence of microsporidiosis in cancer-positive patients are insufficient [28]. It seems that those taking immunosuppressive drugs are more susceptible to infection presumably because their immune response is affected by these drugs [ 19 ]. We found that the prevalence of E. bieneusi was significantly different based on patients' immune state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsporidiosis in immunocompromised patients is characterized by severe and chronic diarrhea with massive weight loss especially in HIV/AIDS patients, as well as nausea, vomiting, malabsorption, and dyspepsia [85][86][87] . In 2017, Kazemi et al [88] reported that multiplex nested PCR targeting internal transcribed spacer (ITS), small subunits (SSU) and large subunits (LSU) of ribosomal DNA (rDNA) identified intestinal Microsporidium with high sensitivity as compared to traditional techniques such as modified trichrome staining. Albendazole is effective against Encephalitozoon (Enc.)…”
Section: Microsporidium Sppmentioning
confidence: 99%